The antecedents of innovative working behavior and its impact on career advancement among academicians in Malaysian Islamic higher learning institutions - Imran , Ayub Ilfandy; Wok, Saodah (2014)
Innovation has been identified as a crucial drive that determines the survival, growth and sustainability of many modern organizations. In today’s competitive environment, innovation can be critical in driving both individual and organizational successes. More importantly, individuals within the organizations are the key player in the implementation of innovativeness at work. Hence, this study investigates the antecedents of innovative working behavior and its impact on career advancement. Specifically, this study will take a close look on how communication efficacy, communication climate, mentoring, and networking influence academicians’ innovative working behavior. These communication factors are believed to provide opportunities for the innovation and implementation of novel ideas that will aid employees in achieving their career goals, and thus become a platform for their career advancement in the organizations. The study adopted a quantitative survey research design. Self-administered questionnaires were distributed to 132 lecturers from three major Islamic universities in Malaysia. The findings indicate that there are significant relationships found between all four communication factors with innovative working behavior. Specifically, this study found that innovativeness is strongly correlated with communication efficacy, communication climate, networking, and moderately correlated with mentoring. This study also found that innovativeness is strongly correlated with career advancement. Furthermore, regression analysis found that networking is the most influential factor to predict innovative working behavior, followed by efficacy and mentoring.